Cutting : a healing response - Lelek, Jeremy, 1973- (Phillipsburg, N.J. : P&R Pub., 2012)
Self-mutilation is a means of dealing with deep, complex emotional turmoil by disfiguring the body with knives, razor blades, or needles. The sufferings of Jesus Christ, however, and the finished work of the Cross offer hope, security, and healing. This booklet illustrates how those struggling with cutting can apply the gospel (death, burial, and resurrection of Jesus Christ) in practical ways to their issues of cutting. --from publisher description
Keywords: Adult child sexual abuse victims -- Religious life; Cutting (Self-mutilation) -- Religious aspects -- Christianity